Gambaran Tingkat Kepadatan Lalat dan Keluhan gangguan Pencernaan pada Pekerja di Satuan Pelayanan Pemenuhan Gizi Kota Manado - Sintike Kumaat; Paul Arthur Tennov Kawatu; Wulan Pingkan Julia Kaunang (KOLONI, 2026)
Flies are disease vectors from the order Diptera, whose presence in the work environment potentially causes health problems, particularly digestive disorders such as nausea, vomiting, and diarrhea, which can ultimately affect worker productivity. Objective: This study aims to describe the fly density level and digestive disorder complaints among workers at the Nutritional Fulfillment Service Unit (SPPG) in Manado City. Methods: This was a quantitative descriptive study with a cross-sectional approach conducted from March to May 2026. The population and sample consisted of all active workers at SPPG X (50 people) and SPPG Y (50 people), totaling 100 respondents who met the inclusion and exclusion criteria. Data were collected through direct observation of fly density and interviews using questionnaires. Data were analyzed univariately to determine frequency distribution. Results: The results showed that fly density levels in both SPPG kitchens were generally in the low category. However, a moderate category was still found in the portioning area at SPPG X and the dishwashing area at SPPG Y. Most workers had digestive disorder complaints in the low category, with gastritis (maag) being the most frequently reported medical history. Conclusion: The fly density level and digestive disorder complaints among workers in both SPPG kitchens in Manado City are generally low, with gastritis being the most frequently reported illness history.